The Relevance of the Student Centered Learning Method in Teaching Islamic Cultural History at MA Al Islamiyah 242 - Primustisio Bintang Mahesa; Nurjanah Nurjanah (IQRO: Journal of Islamic Education, 2026)
This study examines the relevance of Student-Centered Learning (SCL) to the teaching of Islamic Cultural History (Sejarah Kebudayaan Islam, SKI) at MA Al Islamiyah 242. A quantitative survey design was used, with 23 students taken as a total sample. Data were gathered through a closed Likert-scale questionnaire that measured SCL as the independent variable and SKI learning as the dependent variable, then examined through descriptive statistics and Pearson product-moment correlation after the data satisfied the normality assumption. The findings show that SCL implementation falls into the good category, while SKI learning ranges from moderate to good. The Pearson correlation produced r = 0.71 with a significance value below 0.05, pointing to a strong and positive relationship between the two variables, and simple linear regression confirmed that SCL contributes significantly to SKI learning outcomes (B = 0.451, p = 0.001). These results suggest that SCL is a relevant and effective approach for strengthening the quality of SKI instruction at the Madrasah Aliyah level, mainly through greater student activeness, independence, and the repositioning of teachers as facilitators. The main limitation lies in the small and single-site sample, which restricts statistical power and the generalization of the findings to other madrasah settings. Future research involving larger and more varied samples, along with mixed-method designs, is recommended to strengthen the external validity of these conclusions and to explore the mechanisms through which SCL shapes historical understanding and value internalization among students.